Proposed Marketing Strategy to Increase Sales Turnover at Retail Store X Using SWOT and QSPM Analysis - Zulfikar, Muhamad; Sukapto, Paulus (Jurnal Improsci, 2024)
Toko Retail X, a retail store, provides a variety of daily needs. The Southeast Sulawesi province's Baubau City is home to Toko Retail X, which was formed in 2010. Toko Retail X has been around recently. As a result of Toko Retail X's strategy of constantly adding new products, it is believed that the reduction in profitability results from a need for more knowledge about internal and external elements that affect the business environment. Several techniques were used in the study process, such as the QSPM (quantitative strategic planning matrix), SWOT strategy matrix, and analysis of Toko Retail X's internal and external elements. Toko Retail X's advantages and disadvantages are among the identified internal factors. Porter's Five Forces Model, Toko Retail X prospects and threats, and the IE matrix are among the external aspects identified to ascertain the company's current situation. The SWOT and QSPM strategy matrices will also be utilized to develop and choose corporate strategies. Toko Retail X's position in Region II, where this position signifies growth and build, is indicated by the research results. This means that the developed strategy can concentrate on product development to increase the applications of the product, market penetration to grow the existing businesses, and market development to reach new markets with our current products. The eleven options that make up the final approach have been given a ranking. Developing social media to showcase Toko Retail X's details and answer customer inquiries about the products they wish to purchase is the highest ranking.